Comparative Study Of Plant Biodiversity Data Modeling In Research Perspective - Wahid, Mohd Taib; Kamruzzaman, A.Z.M; Mohamed Shariff, Abdul Rashid (Penerbit UTM Press, 2004)
Despite the extensive research has been perform in plant biodiversity area recent years, managing plant biodiversity with database system still poses many challenges. Bio-diversity is the variety of different types of plants species that grows in various landscape. There is phenomenal growth in the area of biodiversity studies, largely motivated by its economic and humanitarian. Various data models, query languages and techniques have been proposed by many researchers. Data models for plant biodiversity have been developed to manage plant information, digital map data, and remotely sensed images. Plant biodiversity databases management systems can become an enabling technology for important applications like Plant biodiversity, Plant Taxonomy, Botanical Information System, Medicinal and Aromatic Plants. Most of the data models are based on relationql model. Relational model can not support temporal data (time), it only supports spatial data (space). Comparison has been made between existing plant biodiversity data model in computer perspective. Incorporation of the plant biodiversity and time can make an enhancement for the Plant biodiversity and analysis and manipulation. Integrate spatial and temporal information, it has becomes a critical issues in designing a data model. After the comparative study addressing the research issues in biodiversity databases but it will muse on the Plant Biodiversity Data Modeling is providing an analysis of challenges set, the problems come across as well as the proposed solutions and the phenomenal. Overviews the advance in plant biodiversity data model research.